Management complexity indicators in public and private schools in two cities in the State of Amapá, Brazil, between 2014 and 2018 (Research, Society and Development, 2020)
The cities of Macapá and Santana are the two largest municipalities in the State of Amapá, located in the northern region of Brazil. A social indicator is the search to measure, both quantitatively and qualitatively, a specific environment with the purpose of informing about a certain aspect of the observed reality. The Complexity of School Management indicator, in basic education, measures the level of complexity of the management of public and private schools, in six levels, through indicators. The objective of this research was to compare the indicators of management complexity in public and private schools in two cities in the state of Amapá, between 2014 and 2018. A qualitative and quantitative research was carried out, whose data were accessed in the INEP database. Schools with a higher level of complexity, possibly, have greater difficulties in achieving better results in the educational context, in view of the greater number of students. The process of continuing education of the faculty is of great importance, since it is associated with good school performance and its consequent effectiveness. Numerous factors, such as precarious access to the internet, scarcity of necessary and adequate equipment, deficient transportation and other emblematic factors contribute negatively to school management.